2016
DOI: 10.21475/poj.09.05.16.pne232
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and drought-induced methylglyoxal detoxification in Brassica spp. and purification of a high active glyoxalase I from tolerant genotype

Abstract: This experiment was conducted to study the role of glyoxalase system in conferring salinity and drought stress in Brassica spp. Two Brassica genotypes viz. BARI Sharisha16 (tolerant) and Tori7 (susceptible) were exposed to salt (16 dS m -1 ) and drought for 2, 4 and 6 days. The comparative study of two Brassica genotypes under salinity and drought stresses revealed that BARI Sharisha16 is more tolerant than Tori7 in both stresses. Under drought stress and salinity stress, Gly I activity increased significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The plants subjected to SS showed high MG accumulation, as was observed in mung bean [ 30 ], Brassica spp. [ 122 ], and tomato [ 10 ] under SS. The glyoxalase system consists of two enzymes (Gly I and Gly II) to detoxify the overgeneration of methylglyoxal (MG) by consuming GSH as a substrate and thereby causes enhanced stress tolerance [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plants subjected to SS showed high MG accumulation, as was observed in mung bean [ 30 ], Brassica spp. [ 122 ], and tomato [ 10 ] under SS. The glyoxalase system consists of two enzymes (Gly I and Gly II) to detoxify the overgeneration of methylglyoxal (MG) by consuming GSH as a substrate and thereby causes enhanced stress tolerance [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, increased GSH content under SS due to GSH treatment reduced the MG accumulation, thereby reducing oxidative stress in the pepper plants. Another strategy to reduce the MG accumulation is to upregulate the glyoxalase-system-related enzymes, Gly I and Gly II, in many plant species under stress conditions [ 122 ]. In the present study, SS increased the activity of Gly I, but decreased that of Gly II in the pepper plants, similar to what was observed in Brassica napus [ 20 ], tomato [ 125 ], and soybean [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences of crop cultivars in their resistance to stress were also indicated to be correlated with accession-dependent efficiency of the glyoxalase systems and thus with tissue levels of MG (Hossain et al 2016 ). It has also been shown that genetically forced increases in expression of GLXI and/or GLXII (Singla-Pareek et al 2003 , 2006 ; Saxena et al 2011 ; Devanathan et al 2014 ; Zeng et al 2016 ; Batth et al 2020 ) may significantly improve plant stress resistance and could help in the development of crop varieties resistant to environmental stresses (Gupta et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%